2014
DOI: 10.1111/azo.12078
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the female reproductive system of the lac insect, Kerria chinensis (Sternorrhyncha, Coccoidea: Kerridae)

Abstract: Ngernsiri, L., Piyajaraprasert ,W., Wisoram,W. and Merritt, D.J. 2014. Structure of the female reproductive system of the lac insect, Kerria chinensis (Sternorrhyncha, Coccoidea: Kerridae). -Acta Zoologica (Stockholm) 00: 000-000.The ovaries of female lac insects, Kerria chinensis Mahd (Sternorrhyncha: Coccoidea: Kerridae), at the last nymphal stage are composed of several balloon-like clusters of cystocytes with different sizes. Each cluster consists of several clusters of cystocytes arranging in rosette form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In K. chinensis, spermatozoa remain congregated in a bundle after excess cytoplasm is eliminated. During mating, the sperm bundles are transferred into the spermatheca of a young female (about 60 days old) whose ovaries have just started developing (Ngernsiri et al 2015). Dissection of the ovaries of older, developing females (about 75 days old) revealed that spermatozoa were present in their lateral oviducts (image not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In K. chinensis, spermatozoa remain congregated in a bundle after excess cytoplasm is eliminated. During mating, the sperm bundles are transferred into the spermatheca of a young female (about 60 days old) whose ovaries have just started developing (Ngernsiri et al 2015). Dissection of the ovaries of older, developing females (about 75 days old) revealed that spermatozoa were present in their lateral oviducts (image not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the recent view is that there are truly only two main reproductive strategies: viviparity and oviparity ( Ostrovsky, 2013 ; Ostrovsky et al, 2016 ). In previous studies, some insects, such as cockroaches ( Warnecke & Hintze-Podufal, 1996 ), aphids ( Ortiz Rivas, Moya & Torres, 2004 ), tsetse flies ( Meier, Kotrba & Ferrar, 1999 ), thrips ( Kranz et al, 2002 ), and scale insects ( Gavrilov & Kuznetsova, 2007 ; Ngernsiri et al, 2015 ), were described as Ovoviviparous species. Scale insects (Hemiptera: Sternorrhyncha: Coccoidea), like many Hemiptera, feed on sap drawn directly from the plant vascular system and secrete a waxy coating for defense; in addition, many scale insect species are major quarantine pests of agricultural or ornamental plants in tropical/subtropical climates as well as in greenhouses in temperate zones worldwide ( Gullan & Kosztarab, 1997 ; Gavrilov-Zimin, 2018 ).…”
Section: Introductionmentioning
confidence: 99%